Nitrogen but not phosphorus addition affects symbiotic N2 fixation by legumes in natural and semi‑natural grasslands located on four continents - Vázquez, Eduardo; Schleuss, Per‑Marten; Borer, Elizabeth T.; Bugalho, Miguel N.; Caldeira, Maria C.; Eisenhauer, Nico; Eskelinen, Anu; Fay, Philip A.; Haider, Sylvia; Jentsch, Anke; Kirkman, Kevin P.; McCulley, Rebecca L.; et al. (Springer Nature, 2022)
The amount of nitrogen (N) derived from symbiotic N2 fixation by legumes in grasslands might be affected by anthropogenic N and phosphorus (P) inputs, but the underlying mechanisms are not known. Methods We evaluated symbiotic N2 fixation in 17 natural and semi-natural grasslands on four continents that are subjected to the same full-factorial N and P addition experiment, using the 15N natural abundance method. Results N as well as combined N and P (NP) addition reduced aboveground legume biomass by 65% and 45%, respectively, compared to the control, whereas P addition had no significant impact. Addition of N and/or P had no significant effect on the symbiotic N2 fixation per unit legume biomass. In consequence, the amount of N fixed annually per grassland area was less than half in the N addition treatments compared to control and P addition, irrespective of whether the dominant legumes were annuals or perennials. Conclusion Our results reveal that N addition mainly impacts symbiotic N2 fixation via reduced biomass of legumes rather than changes in N2 fixation per unit legume biomass. The results show that soil N enrichment by anthropogenic activities significantly reduces N 2 fixation in grasslands, and these effects cannot be reversed by additional P amendment.